Strategi Kepemimpinan Kepala Sekolah Dalam Meningkatkan Prestasi Akademik Siswa Melalui Nilai Kearifan Lokal Waja Sampai Kaputing - Rahmi, Agustina; Redjeki , Dwi Sogi Sri; Eshariyani, Eshariyani; Rasuna, Rasuna; Husnusyaziah, Husnusyaziah; Mardani, Mardani (Jurnal Ilmiah Kanderang Tingang, 2024)
The aim of this research is to explore the principal's leadership strategies in improving student academic achievement at SMAN 3 Banjarbaru, as well as identifying inhibiting factors and the solutions offered. This research uses qualitative methods with data collection techniques including observation, interviews and documentation. The results of the research show that the strategy used by the Principal of SMAN 3 Banjarbaru is by conducting a SWOT analysis, establishing a vision, mission and making a strategic plan by carrying out effective communication through the waja to kaputing philosophy and creating a supportive environment and approaching students both internally and external. Meanwhile, the implementation carried out by the school principal is by listening to opinions, accommodating needs and ensuring the commitment of all school members. Meanwhile, the solution taken by the school principal if there are challenges and obstacles is to carry out analysis, provide solutions and provide guidance and follow-up.